Filmes nanocompósitos à base de celulose bacteriana e nanocristais de celulose - Nascimento, Elígenes Sampaio do (2018)
One of the most serious environmental problems facing society today is pollution mainly caused by packaging for food produced from non-biodegradable sources. In this sense, attention is focused on the use of biopolymer materials in the production of environmentally correct nanocomposite systems, such as bacterial cellulose. The bacterial cellulose (CB) is non-toxic, biocompatible, biodegradable, and has a naturally nanosized three-dimensional network, which gives it high crystallinity and mechanical resistance, properties that qualify CB as a promising material for application in nanocomposites. The objective of this study was to develop nanocomposite films of all cellulose by means of chemical and physical disintegration routes to obtain nanocrystals and nanofibrils, respectively, from a bacterial cellulose disintegration approach. Additionally, the use of nanocrystals in the film-forming suspension for film production was evaluated, as well as the use of ultrasound in their dispersion. The films were characterized chemically, physically and morphologically, as well as their in vitro cytotoxicity considering a future application in food packaging. The nanofibers presented a high crystallinity index (84%), good suspension stability (Zeta = -58 mV), characteristic morphology of CB, with a 41% reduction in width of the nanofibers (40 nm). The all cellulose composite films were opaque and yellowish-looking, hydrophilic, insoluble in water - insoluble matter ranging from 88 to 93% - high crystallinity (mean crystallinity index = 84%), good thermal stability, resistant, rigid, with little deformation and non-toxic to Caco-2 cells. The results showed that it is possible to combine TEMPO radical-mediated oxidation and high-rotation mixer to obtain cellulose nanofibers, as well as, from nanofibrillated oxidized bacterial cellulose (CBOXNF), to produce films with exceptional characteristics without the addition of cellulose nanocrystals, which can reduce production costs, making it an even more attractive material.